QUANTIFICATION CONTRASTS OF LEXICAL MICROSYSTEMS WITH SYNONYMS SЪVEDETELЬ – POSLUKHЪ (A WITNESS) AND THEIR DERIVATIVES IN THE OLD EAST SLAVIC WRITTEN SOURCES (BASED ON MANUSCRIPT HISTORICAL CORPUS) - Oleg F. Zholobov (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article makes the first attempt to describe transformations of lexical series with a synonymous pair sъvědětelь – poslukhъ (‘a witness’) and their derivatives sъvědětelьstvo, sъvědětelьstvovati – poslušьstvo, poslušьstvovati in Old East Slavic written sources. The study uses the Manuscript Historical Corpus. For analysis, the author chose Gospel, Apostolos, Parimejnik, Parenesis of Ephraim the Syrian, and chronicles subcorpora; the data from everyday writing and documentation were also studied. Quantification is a measurement of synonymous lexemes ratio that enables discovering lexical microsystems’ status in texts and the trends of their transformations in the Old East Slavic period, which predetermined the position of the lexemes in the contemporary vocabulary. The lexeme sъvědětelь was not used in birch bark letters and early East Slavic documentation, neither were its derivatives sъvědětelьstvo and sъvědětelьstvovati. In church-associated written sources, the pair sъvědětelь – posluchъ, together with their derivatives, correlate with the Cyril-and-Methodius and Preslav translation traditions. In the church written tradition, the ratio of lexemes in the corresponding lexical series is expressed by contrasting quantitative formulas that reflect the text-critical history, genre-stylistic nature, and discursive dominants of the texts. Thus, quantitative formulas are shown to be important characterizing markers of written sources. The article specifies grounds and chronology of the first examples of the bookish lexeme sъvědětelь transforming into the neutral svidětel’, which replaced the East Slavic analogue posluchъ during the competitive confrontation of denotative images.